PENDIDIKAN AGAMA ISLAM TRANSFORMATIF:MEMBANGUN DIGITAL ETHICS QUOTIENT (DEQ) MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL): (Transformative Islamic Religious Education: Building Digital Ethics Quotient (Deq) Through A Contextual Teaching And Learning (Ctl) Approach) - Arief Nur Rohman (Raqib: Jurnal Studi Islam, 2025)
Digital disruption has brought significant ethical challenges for the younger generation. This study aims to offer pedagogical solutions through the integration of the Transformative PAI model with the Contextual Teaching and Learning (CTL) approach to holistically build students' Digital Ethics Quotient (DEQ). The proposed research method is classroom action research (CAR) with a cycle based on contextual reflection, focusing on the implementation of PAI based on real digital ethics scenarios. Initial results show that there is a connection between normative PAI material and contemporary digital issues (such as cyberbullying, fake news, and data privacy). Through CTL, ethical awareness, critical thinking skills, and students' ability to make moral decisions in the digital space can be significantly improved. The results of a questionnaire distributed to 72 elementary school students showed that 89.5% of students, or approximately 64 students, demonstrated integrity (honesty and trustworthiness) and were able to respect privacy. Meanwhile, the remaining 10.5%, or approximately 8 students, did not yet demonstrate integrity and respect for privacy. This article concludes that Transformative PAI-CTL is a solution-oriented and relevant model for internalizing religious values into concrete digital ethical actions, transforming students from mere users into responsible digital citizens.